Real-world effectiveness of biological therapy in patients with rheumatoid arthritis: Systematic review and meta-analysis - Caroline Tianeze de Castro; Mariana Jorge de Queiroz; Flavia Caixeta Albuquerque; Celmário Castro Brandão; Leticia Farias Gerlack; Daniella Cristina Rodrigues Pereira; Sandra Castro Barros; Wenderson Walla Andrade; Ediane de Assis Bastos; Jessé de Nobrega Batista Azevedo; Roberto Carreiro; Mauricio Lima Barreto; et al. (Frontiers Media S.A., 2022)
Background: The treatment of rheumatoid arthritis (RA), a chronic systemic inflammatory autoimmune disease, is based on disease-modifying anti-rheumatic drugs (DMARDs). Typically, it starts with conventional synthetic DMARDs (csDMARDs), and depending on the patient's response to the treatment and the adverse events experienced, biological DMARDs (bDMARDs) are initiated. bDMARDs are more specific to inflammatory factors than csDMARDs and more efficient in inducing remission and low disease activity. Thus, this study aimed to assess the effectiveness of biological therapy in patients with rheumatoid arthritis in administrative health databases.Methods: PubMed, Embase, Lilacs, Ovid, Scopus, and Web of Science databases were searched from inception to 21 October 2021, to identify observational studies that evaluated the effectiveness of biological therapy in patients with rheumatoid arthritis using administrative databases and real-world data. The methodological quality was assessed by the methodological index for non-randomized studies (MINORS). A fixed or random-effects model estimated risk ratios with 95% confidence intervals. The analysis was divided into four groups: tumor necrosis factor inhibitors (TNFi) versus non-TNFi; TNFi versus TNFi (adalimumab, etanercept, and golimumab versus infliximab); bDMARDs versus Janus kinase inhibitors (JAKi); and bDMARDs monotherapy versus combination therapy (bDMARDs and MTX).Results: Twenty-one records were eligible for inclusion in this systematic review and meta-analysis; seven population-based cohorts, eight prospective, and six retrospective cohort studies. Overall, 182,098 rheumatoid arthritis patients were evaluated. In the meta-analysis, lower effectiveness was observed among TNFi users than in non-TNFi (RR: 0.88; 95% CI: 0.81-0.95; p < 0.01; I2 = 94.0%) and bDMARDs than in JAKi (RR: 0.86; 95% CI: 0.79-0.94; p < 0.01; I2 = 93.0%). Higher effectiveness among adalimumab, etanercept, and golimumab than in infliximab (RR: 1.19; 95% CI: 1.05-1.36; p < 0.01; I2 = 96.0%) was found. No significant differences in the effectiveness of bDMARD monotherapy compared to combination therapy (RR: 0.83; 95% CI: 0.68-1.00; p < 0.01; I2 = 81.0%) was observed. E-value analysis indicated that the estimates were not robust against unmeasured confounding.Conclusion: According to the available real-world data, our results suggest that biological therapy effectively treats patients with rheumatoid arthritis, indicating higher effectiveness with non-TNFi and JAKi than with TNFi.Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php?ID#CRD42020190838, identifier CRD42020190838.